A study of cord blood albumin as a predictor of significant neonatal hyperbilirubinemia in term and preterm neonates - Reshad, Mohamed; Ravichander, Balasundaram; Raghuraman, Thiruchinappalli Subramaniam (International Journal of Research in Medical Sciences, 2016)
Background: Neonatal hyperbilirubinemia (NH) is the commonest abnormal physical finding which affects nearly 60% of term and 80% of preterm neonates during the first week of life. Although hyperbilirubinemia is more prevalent in preterm infants due to multiple factors, it can occur even in healthy term infants. Albumin is synthesized by liver and it helps in transport of unconjugated bilirubin. Early prediction of hyperbilirubinemia will help in early discharge and prevent hospitalization of babies and mothers for a longer period. Methods: Observational study was performed on 175 newborns, divided in to term and preterm. Cord blood was collected from the newborns for cord serum albumin level measurements. Total serum bilirubin was measured during 72-96 hours of life, or earlier if clinically indicated, and assessed clinically daily for NH and intervened. Results: Study cohort was grouped in to term and preterm, and each was further divided into 3 groups based on Cord Blood Albumin level (CBA) ≤2.8 g/dL, 2.9-3.3 g/dL and ≥3.4 g/dL, respectively. In these groups, the CBA levels of newborns with significant hyperbilirubinemia that required intervention was correlated with cord serum albumin levels. It showed that CBA level ≤ 2.8 g/dL is critical, with a good sensitivity and positive predictive value, in both term and preterm neonates. CBA level ≥ 3.4 g/dL was found to be relatively safe for neonates. Conclusions: There is a correlation between CBA level and hyperbilirubinemia in both term and preterm newborns. Cord blood albumin level of ≤2.8 g/dL can predict the development of neonatal hyperbilirubinemia.